Greening health care : how hospitals can heal the planet - Gerwig, Kathy (Oxford University Press, 2015)
"The relationship between hospitals and the environment is defined by a glaring contradiction: as health care facilities deliver care at any cost, their environmental footprint -- pollution, waste production, unsustainable food services -- contributes to harming community health. Greening Health Care examines the intersections of health care and environmental health, both in terms of traditional failures and the revolution underway to fix them. Authored by one of the pioneers in health care's green movement, it presents practical solutions for health care organizations and clinicians to improve their environments and the health of their communities. Topics include: making food services sustainable, managing hospital waste, and relevant impacts/mitigating measures related to climate change. As environmental protection grows into an imperative for all aspects of society, Greening Health Care offers an historical and practical approach to sustainable health care delivery"--Publisher's description